Investigating the Phenomena of Women in Lone Wolf Terrorism in Indonesia - Beny Abukhaer Tatara; Wahyu Sekti Retnaningsih (Sultan Publisher, 2022)
This study aims to investigate The phenomenon of increasing women's involvement in acts of terrorism, especially